Application of Certain π-Acceptors for the Spectrophotometric Determination of Alendronate Sodium in Pharmaceutical Bulk and Dosage Forms - Asad Raza; Muhammad Zia-ul-Haq (International Journal of Analytical Chemistry)
Two simple, fast, and accurate spectrophotometric methods for the determination of alendronate sodium are described. The methods are based on charge-transfer complex formation of the drug with two π-electron acceptors 7,7,7,8-tetracyanoquinodimethane (TCNQ) and 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) in acetonitrile and methanol medium. The methods are followed spectrophotometrically by measuring the maximum absorbance at 840 nm and 465 nm, respectively. Under the optimized experimental conditions, the calibration curves showed a linear relationship over the concentration ranges of 2–10 μg mL−1 and 2–12 μg mL−1, respectively. The optimal reactions conditions values such as the reagent concentration, heating time, and stability of reaction product were determined. No significant difference was obtained between the results of newly proposed methods and the B.P. Titrimetric procedures. The charge transfer approach using TCNQ and DDQ procedures described in this paper is simple, fast, accurate, precise, and extraction-free.